The New Reality of Infective Endocarditis: Changes in Patient Demographics and Outcomes in South Carolina - Grant Garrison; Julie Royer; Max Habicht; Sarah Battle; Hana R. Winders; Kayla Antosz; Anna-Kathryn Burch; Majdi N. Al-Hasan; Julie Ann Justo; Pamela Bailey (Infectious Disease Reports, 2025)
Background: Rising rates of opioid use disorder (OUD), usually via injection, has resulted in younger patients being diagnosed with infective endocarditis (IE), with unique treatment challenges. Methods: This retrospective ecological study analyzed hospital discharge and home health records from 2016 to 2022 in South Carolina (SC). Cases of IE with concurrent coding for OUD were identified. Differences in patient demographics, hospital characteristics, length of care days, and charges by OUD status were determined using chi-square or t-tests. IE hospitalization rates by OUD status, year, and age group were calculated, and linear regression was used to determine differences by year. Results: There were 8601 acute-care hospitalization records for IE from 2016 to 2022 in the SC dataset, of which 1180 (13.7%) had concurrent OUD coding. Statistically significant differences between patients with and without OUD were identified for sex, age group, race, resident rurality, average number of comorbidities, disposition status, and year (all p < 0.01). The incidence rate of IE increased from 2.5/100,000 in 2016 to 6.9/100,000 in 2022 in patients aged 36 to 49 years with OUD (p = 0.02). Patients with IE and OUD who were discharged home had significantly longer lengths of stay in acute care hospitals (32.9 vs. 15.3 days; p < 0.01) and excessive hospital charges ($308,874 vs. $188,862) compared to those without OUD. Conclusions: Major changes have occurred in the demographics of IE in SC. The increasing incidence rate of IE in younger adults with OUD coupled with prolonged stays at acute care hospitals pose challenges to the healthcare system that require creative solutions.